THE IMPORTANCE OF EDUCATION FINANCING MANAGEMENT IN THE MANAGEMENT OF EDUCATIONAL INSTITUTIONS - Faisal Irsandi; Ulfiyyatur Rosyidah; Imelda Dian Rahmawati; Hidayatulloh (International Journal of Economic Integration and Regional Competitiveness, 2024)
Financial management in education is the process of planning, organizing, controlling, and monitoring financial resources used to finance educational activities. This research aims to identify the importance of financial management in education through a literature review. The research method used is a literature review, which is an analysis of sources of information derived from literature or documents related to the research topic. The sources of information used in this study consist of scholarly journals, books, and documents related to financial management in education. The results of the study indicate that financial management in education plays a crucial role in ensuring the smoothness and success of the learning process. Good financial management will ensure that available funds are used effectively and efficiently, thereby improving the quality of education. Financial management also allows schools to manage financial risks, such as unexpected costs or funding shortages. Financial management in education also plays a vital role in ensuring fair and equitable access to education for all students. With good financial management, schools can provide equal opportunities for all students to obtain quality education. In conclusion, financial management in education is essential to ensure the success of the learning process and equitable access to education. Therefore, effective and efficient financial management is required in education. This research recommends that the government and educational institutions evaluate and improve existing financial management systems, as well as increase transparency and accountability in the use of education funds.